Zoology Section, Biological Research Division, BCSIR Laboratories, Dhaka,Qudrat-E-Khuda Road, Dhanmondi, Dhaka-1205, Bangladesh (The Journal of Plant Protection Sciences, 2021)
The role of weather factors, such as temperature, total rainfall, number of rainy days and relative humidity on the  development of diseases like canker (Pestalotia psidii), anthracnose and die back (Colletotrichum gloeosporioides),  stem canker and dry fruit rot (Botryodiplodia theobromae) and Phytophtora fruit rot (Phytophthora nicotianae var  Parasitica) of guava were analysed for predictive purpose from regression equations. The simple correlation coefficient  matrix showed significantly positive correlation of canker severity with maximum relative humidity at 1% level  whereas, anthracnose correlated well with minimum relative humidity, temperature and number of rainy days at 5%  level.The negative correlation was obtained for stem canker and dry rot with all parameters at 1% significant level. In  case of Phytophthora fruit rot, positive correlation was also recorded with all parameters, except maximum relative  humidity.
Keywords: Disease prediction model; weather parameters; Pestalotia psidii; Colletotrichum gloeosporioides; Botryodiplodia theobromae; Phytophthora nicotianae var parasitica